Phytoplankton Community Response to Changes in Light: Can Glacial Rock Flour Be Used to Control Cyanobacterial Blooms? - Gaskill, Jacob A.; Harris, Ted D.; North, Rebecca L. (Frontiers in Environmental Science, 2020)
Cyanobacterial harmful algal blooms are one of the most prominent threats to water quality in freshwater ecosystems and are expected to become more common as the climate continues to change. While traditional strategies to manage algal blooms have focused on controlling nutrients, manipulating light as a way to reduce cyanobacteria is less frequently explored. Here, we propose the addition of glacial rock flour (GRF), a fine particulate that floats on the water’s surface and remains suspended in the water column, to reduce light availability and in turn, phytoplankton biomass dominated by cyanobacteria. To determine if a sustained reduction in light could reduce cyanobacteria biomass and associated cyanotoxins, we applied GRF to mesocosm tanks for 9 consecutive days. Mesocosm tanks were amended with nitrogen and phosphorus to generate chlorophyte- and cyanophyte-dominated experimental tanks. To assess how the phytoplankton community was impacted in each tank, we measured photosynthetic irradiance parameters, the maximum quantum yield of photosystem II, gross primary productivity (GPP), phytoplankton biovolume, and phytoplankton community composition before and after the addition of GRF. GRF effectively reduced cyanophyte biovolume by 78% in the cyanophyte-dominated tanks, despite no significant change in total phytoplankton community biovolume. Cyanophytes were replaced by cryptophytes, which increased by 106% in the chlorophyte-dominated tanks and by 240% in the cyanophyte-dominated tanks. The change in photosynthetic irradiance parameters and GPP after the addition of GRF was not significantly different between any of the experimental groups, suggesting that either the cyanophytes will likely recover if light availability increases, or that the new cryptophyte-dominated community was well suited to a reduced light environment. Cyanobacterial blooms are expected to increase in frequency and magnitude as climate change progresses, but our study suggests that light manipulation may be a useful in-lake management strategy for controlling these blooms and warrants further investigation.